2018
DOI: 10.1080/02827581.2018.1479442
|View full text |Cite
|
Sign up to set email alerts
|

Skepticism of state action in forest certification and voluntary set-asides: a Swedish example with two environmental offsetting options

Abstract: Non-industrial private forest owners in Sweden are encouraged to mitigate environmental damages from forestry on their properties under a principle of "freedom with responsibility," although the level of mitigation is generally left to the owners' discretion. One voluntary measure private forest owners are encouraged to take is setting aside a part of their productive forests for conservation. The purpose of this paper is to evaluate how non-industrial private forest owner beliefs concerning both their own and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…This also indicates that underlying ideals and values are not a su ciently strong motivator for undertaking management treatments to achieve the desired change compared to the act of certifying or becoming member within a forest owner association. Our ndings are corroborated by Danley (2018) who found that forest owners who where members of an FOA were also more frequently certi ed, and therefore also retained more set-asides.…”
Section: Societal Challenge # 1: Climate Changesupporting
confidence: 84%
“…This also indicates that underlying ideals and values are not a su ciently strong motivator for undertaking management treatments to achieve the desired change compared to the act of certifying or becoming member within a forest owner association. Our ndings are corroborated by Danley (2018) who found that forest owners who where members of an FOA were also more frequently certi ed, and therefore also retained more set-asides.…”
Section: Societal Challenge # 1: Climate Changesupporting
confidence: 84%
“…Previous literature suggests that females, resident forest owners, and non-members of forest owners' association are more likely to adopt forest management practices promoting carbon sequestration, climate change adaptation, or biodiversity (Matta et al, 2009;Danley, 2018;Juutinen et al, 2020). Moreover, regarding gender, forests owned by males are more actively managed (Lidestav & Berg Lejon, 2013), females sell timber less frequently (Kuuluvainen et al, 2014), and males are more often compensation oriented in terms of biodiversity conservation in commercial forests (Koskela & Karppinen, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The role of forest property size in forest management behavior is ambiguous and varies between forest management practices. Large forestland size is positively associated with leaving unmanaged areas (Danley, 2018) and converting monocultures to mixed broadleaved stands (Van Herzele & Van Gossum, 2009), while the effect on the delayed harvest is ambiguous (Khanal et al, 2017;Mäntymaa et al 2018;Kline et al 2000a). In this study, the effect of property size on adopting the forest management practices studied is generally negative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations